PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI UNTUK MENGEMBANGKAN KOMPETENSI PEDAGOGIK GURU - Rahma, Maulitha; Yulis, Erna; Pratiwi, Neisya; Susanto, Ratnawati; Syofyan, Harlinda (Eduscience : Jurnal Ilmu Pendidikan, 2021)
AbstractIn the current era of globalization, a teacher must have pedagogical competence in utilizing information and communication technology. We can conclude that teachers' pedagogical competence in utilizing information and communication technology plays an important role in the success of the learning process, therefore teachers are required to operate computers and communicate to students in delivering material well. The main research problems can be formulated as follows: (1) What is the description of the use of the communication model as a teacher pedagogic developer? (2) What is the description of using a model based on instructional communication patterns as a teacher pedagogic developer? The objectives of this study are: (1) To describe the use of the communication model as a teacher pedagogic developer. (2) To describe the use of a model based on instructional communication patterns as a teacher pedagogic developer. The results of communication research between teachers and students can be concluded: (1) Teachers use reading / writing more (2) Teachers use more and activities in conveying information to students. (3) The teacher prefers to use dialogical openness, interpersonal communication, group, informative, ideas, persuasive, politeness, expression, mentoring, and student-teacher oriented. Keywords: communication, pedagogic competence, teacher AbstrakDi era perkembangan globalisasi saat ini, seorang guru harus memiliki kompetensi pedagogik dalam memanfaatkan teknologi informasi dan komunikasi. Bisa kita simpulkan bahwa kompetensi pedagogik guru dalam memanfaatkan teknologi informasi dan komunikasi sangat berperan penting dalam keberhasilan proses pembelajaran, oleh sebab itu guru dituntut untuk mengoperasikan computer dan berkomunikasi kepada peserta didik dalam penyampaian materi dengan baik. Dapat dirumuskan permasalahan pokok penelitian sebagai berikut: (1) Bagaimana gambaran pemanfaatann model komunikasi sebagai pengembang pedagogik guru? (2) Bagaimana gambaran pemanfaatann model berbasis pola komunikasi instruksional sebagai pengembang pedagogik guru? Tujuan penelitian ini yaitu: (1) Untuk menggambarkan pemanfaatann model komunikasi sebagai pengembang pedagogik guru. (2) Untuk menggambarkan pemanfaatann model berbasis pola komunikasi instruksional sebagai pengembang pedagogik guru. Hasil penelitian komunikasi antar guru dan peserta didik dapat disimpulkan: (1) Guru lebih menggunakan bacaan/tulisan (2) Guru lebih menggunakan dan aktivitas dalam menyampaikan informasi kepada peserta didik. (3) Guru lebih menggunakan keterbukaan dialogis, berkomunikasi anta-pribadi, kelompok, informatif, ide, persuasif, kesantunan, pengukapan, pendampingan, dan student-teacher oriented. Kata kunci: komunikasi, kompetensi pedagogik, guru